2021
DOI: 10.1038/s41586-021-04031-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct limits for scalar field dark matter from a gravitational-wave detector

Abstract: The nature of dark matter remains unknown to date, although several candidate particles are being considered in a dynamically changing research landscape1. Scalar field dark matter is a prominent option that is being explored with precision instruments, such as atomic clocks and optical cavities2–8. Here we describe a direct search for scalar field dark matter using a gravitational-wave detector, which operates beyond the quantum shot-noise limit. We set new upper limits on the coupling constants of scalar fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 44 publications
0
51
0
Order By: Relevance
“…For typical laser frequencies and common dielectric materials, changes in n are generally sub-dominant compared to adiabatic changes in l [59,433], but can become dominant at frequencies far above the fundamental frequency associated with the relevant mechanical resonance of the material [59]. Searches for scalar UDM with Michelson interferometers have been recently performed using older datasets from GEO600 [444] and the Fermilab holometer [445]; see Figs. 11 and 12 for limits on the linear scalar-electron interaction.…”
Section: Optical Interferometers (Including Gravitational-wave Detect...mentioning
confidence: 99%
See 2 more Smart Citations
“…For typical laser frequencies and common dielectric materials, changes in n are generally sub-dominant compared to adiabatic changes in l [59,433], but can become dominant at frequencies far above the fundamental frequency associated with the relevant mechanical resonance of the material [59]. Searches for scalar UDM with Michelson interferometers have been recently performed using older datasets from GEO600 [444] and the Fermilab holometer [445]; see Figs. 11 and 12 for limits on the linear scalar-electron interaction.…”
Section: Optical Interferometers (Including Gravitational-wave Detect...mentioning
confidence: 99%
“…Figs. 11 and 12 show limits from searches for EP violation [30,42,451,452,454,673], atom-cavity experiments [58,60,311,438,439], molecular iodine (I 2 ) experiments [44], the AURIGA experiment [472], optical interferometry experiments [444][445][446], atom interferometry experiments [412], the stellar cooling bounds [274], and astrophysical constraints [19,21,22,24,145,230,239]. Fig.…”
Section: Combined Exclusion Plots and Projections For Future Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…where Λ QCD is the QCD scale and m q is the averaged light quark mass. There are now many dedicated experiments searching for these types of signals [52][53][54][61][62][63][64][65][66][67][68][69][70][71][72][73].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a GW experiment can also be used to look for dark matter candidates, in both ultraheavy (see Ref. [30] and references therein) and ultralight [31][32][33][34][35][36] mass regions. So far, most of the PBH searches using SGWB are focused on PBH-PBH mergers.…”
Section: Introductionmentioning
confidence: 99%